1991
DOI: 10.1126/science.1990432
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Computational Maps Control Auditory Perception

Abstract: Mustached bats orient and find insects by emitting ultrasonic pulses and analyzing the returning echoes. Neurons in the Doppler-shifted constant-frequency (DSCF) and frequency-modulated (FM-FM) areas of the auditory cortex form maps of echo frequency (target velocity) and echo delay (target range), respectively. Bats were trained to discriminate changes in echo frequency or delay, and then these areas were selectively inactivated with muscimol. Inactivation of the DSCF area disrupted frequency but not delay di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…Although the auditory cortex may simply reflect properties of periodicity coding generated in the midbrain, the auditory cortex is crucial for relating an auditory representation to behavior (Heffner and Heffner, 1990;Riquimaroux et al, 1991;Smith et al, 2004). It has been suggested that the role of the auditory cortex might be to organize sound features already extracted by lower levels into auditory objects (Nelken, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the auditory cortex may simply reflect properties of periodicity coding generated in the midbrain, the auditory cortex is crucial for relating an auditory representation to behavior (Heffner and Heffner, 1990;Riquimaroux et al, 1991;Smith et al, 2004). It has been suggested that the role of the auditory cortex might be to organize sound features already extracted by lower levels into auditory objects (Nelken, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is especially interesting to directly relate neural processing to behavioral performance, an attempt that has only been made a few times in bats (Riquimaroux et al, 1991(Riquimaroux et al, , 1992. Thus, two questions are pursued here: (1) what are the behavioral thresholds for auditory-object discrimination based on IR roughness in P. discolor and (2) is there an auditory cortical correlate of the behavioral performance?…”
Section: Introductionmentioning
confidence: 99%
“…The FM/FM area was proven to be instrumental for discriminating between echo delays during a fear conditioning task 8 . However, the mechanisms by which this area-and the map it contains-yields a representation of acoustic scenes during echolocation remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical delay-tuned neurons of the species Pteronotus parnellii, Pteronotus quadridens, Carollia perspicillata and Rhinolophus rouxi are confined to a specialized region in the dorsal auditory cortex defined as the frequencymodulated (FM)/FM processing area [4][5][6][7] . Some empirical evidence suggests that the FM/FM area has a role in the bat's perception of echo delay 8 .…”
mentioning
confidence: 99%
“…Neurons responding to different echo delays are chronotopically arranged so that a continuous representation of echo delay time is created on the cortical surface 6,10 . For PP, it has been demonstrated that delay-tuned neurons are crucial for temporal discrimination behaviour 11 .…”
mentioning
confidence: 99%